Bromolactamization: Key Step in the Stereoselective Synthesis of Enantiomerically Pure, cis‐Configured Perhydropyrroloquinoxalines. Issue 12 (5th July 2014) - Schulte, Adrian; Situ, Xingci; Saito, Susumu; Wünsch, Bernhard
ABSTRACT Compounds based on the pyrroloquinoxaline system can interact with serotonin 5‐HT3, cannabinoid CB1, and μ‐opioid receptors. Herein, a chiral pool synthesis of diastereomerically and enantiomerically pure bromolactam (S, R, R, R)‐14A is presented. Introduction of the cyclohexenyl ring at the N‐atom of (S)‐proline derivatives 8 or methyl (S)‐pyroglutamate (12) led to the N‐cyclohexenyl substituted pyrrolidine derivatives 4 and 13, respectively. All attempts to cyclize the (S)‐proline derivatives 4 with a basic pyrrolidine N‐atom via [3 + 2] cycloaddition, aziridination, or bromolactamization failed. Fast aromatization occurred during treatment of cyclohexenamines under halolactamization conditions. In contrast, reaction of a 1:1 mixture of diastereomeric pyroglutamates (S, R)‐13bA and (S, S)‐13bB with LiOtBu and NBS provided the tricyclic bromolactam (S, R, R, R)‐14A with high diastereoselectivity from (S, R)‐13bA, but did not transform the diastereomer (S, S)‐13bB. The different behavior of the diastereomeric pyroglutamates (S, R)‐13bA and (S, S)‐13bB is explained by different energetically favored conformations. Chirality 26:793–800, 2014. © 2014 Wiley Periodicals, Inc.